Зрадник чи жертва. Юда Іскаріот в українському мистецтві XV–XVIII ст. (за матеріалами наукового повідомлення на засіданні Президії НАН України 13 грудня 2017 року) - Лесів, А.П. (Вісник НАН України, 2018)
Доповідь присвячено особливостям іконографії Юди Іскаріота в українському малярстві XV—XVIII ст. та символіки його образу. Проаналізовано
збережені пам’ятки іконопису і гравюрні взірці з музейних та приватних
зібрань, з іконостасів та розписів храмів України і Польщі. Обґрунтовано
особливості оригінального образу Юди в українському мистецтві, яке
сформувалося на стику східної та західної мистецьких традицій. Оригінальність образу Юди в українській іконографії проявляється насамперед
у його зовнішності, міміці, жестах, кольоровому трактуванні. В українських іконах образ Юди Іскаріота став своєрідним «дзеркалом», у якому
відобразився універсальний і зрозумілий для простих людей образ грішної
людини, кривдника. Образ Юди вийшов за межі іконографії і став багаторівневим актуальним елементом культури. The paper aims to identify the special iconography of Judas Iscariot in Ukrainian painting of 15th—18th centurіеs, the
symbolism of his image, specific philosophical and theological interpretation of Judas’ figure. The study collects and analyzes
dozens of preserved works of sacral art from museums and private collections, from iconostasis and murals in temples
in Ukraine and Poland. The author systematized literature sources of iconography and symbolism of Iscariot’s image.
It is traced the history of the formation and main features of the image of Judas in the Byzantine and Western European
art. The author’s special attention is paid to interpretation of Judas Iscariot’s symbolic gestures and to symbolism
of his image’s color depiction. The image of Judas Iscariot in Ukrainian 15th—18th centuries painting developed into
original image type of Apostle-traitor. Its iconography was formed at the intersection of Byzantine canon and Western
artistic traditions. Specificity of Judas Iscariot’s image in Ukrainian art is as follows. Originality of Judas’ iconography
comes out from his appearance, facial expressions, gestures, color interpretation. In terms of the symbolism of the Judas’
image, in Ukrainian icons Judas Iscariot became a kind of "mirror" which reflected the universal and understandable for
ordinary people symbol of sinful man or the offender. Image of Judas Iscariot became not only just iconography motif, but
also a relevant element of culture.